Peran Guru Membangun Komunikasi Siswa di MTs Yasmida Ambarawa - Miftahudin, Miftahudin; Umurohmi, Ulfah; Zainuri, Ahmad (Universitas Pahlawan Tuanku Tambusai, 2025)
This research aims to examine the role of teachers in building effective communication with students at Madrasah Tsanawiyah Yasmida Ambarawa, as well as to identify the challenges faced in this process. Good communication between teachers and students is very important in creating a conducive learning environment, especially at the Madrasah Tsanawiyah level which involves the teenage transition. The research method used was descriptive qualitative with semi-structured interviews and direct observation in classes 8A and 9B. The research results show that although most teachers have tried to create an open and comfortable atmosphere in the classroom, several challenges still arise, such as differences in students' social and cultural backgrounds and the influence of technology which reduces face-to-face interaction. Teachers play a role not only as teachers, but also as mentors who support students' academic, social and emotional development. This research provides insight into the importance of improving teacher communication skills to create a more inclusive learning environment and support successful learning.